Physicochemical qualities of black pepper and coriander treated with low-energy electron beam - Kotilainen, Heidi (fi=Turun yliopisto|en=University of Turku|, 2017)
Spices are used worldwide to improve the sensorial properties of foods. However, they may pose a source of microbial contamination for foods they are added to. The current decontamination technologies for dry foods, such as spices, are not sustainable and are often associated with drawbacks that may result in the alteration of the quality. In dry foods microorganisms reside on the surface of the food material. Low-energy electrons (≤300keV) reach only the surface of food and the quality changes are expected to be much more limited than those caused by other treatments. The aim of the study was to compare and evaluate the effects of different decontamination methods: steam, high-energy electron beam, and low-energy electron beam on the physicochemical qualities of black pepper and coriander. The effects of different treatments on the quality attributes (moisture content, color, essential oil yield and composition, and volatile profiles) of black pepper and coriander were compared and evaluated. Moisture content of the samples was measured with TGA and Hunter’s color parameters were used to determine color attributes. Essential oil composition was analysed by GC-FID and identified with GC-MS as well as volatile profiles. In addition, “electronic nose” (Smart Nose®) was used to detect differences in odor after the treatments. The results indicate that low-energy electron beam has no or minimal effect on the color, moisture and essential oil composition of black pepper and coriander. Also, low-energy electron beam seems to enhance the volatile profiles of the samples. This study illustrates that low-energy electron beam as a gentle and non-thermal decontamination technology for spices can not only improve food safety and sustainable food processing but also improve and maintain the quality.